Investigation of thin wall ductile iron parameter - Mohd Khairi, Mohd Noor (2009)
This thesis deals with thin wall ductile iron parameter.There are two main objectives of this research,firstly, to investigate the processing parameter of thin wall ductile iron by using Sandwich method and to investigate the process design parameter for thin wall ductile iron.The cast iron has graphite in a matrix called pearlitic. The graphite shape is flake which is has lower strength. The study of graphite changes from flake form to nodular form by adding magnesium ferrosilicon as inoculation agent is under consideration. The ductile iron form is enhanced in strength and other mechanical properties. However, the thickness of thin wall is related to the composition of the magnesium adding.Green sand casting is one of the method for converting cast iron to ductile iron.The thesis describes the method of green sand casting by using Sandwich technique to get the thin wall ductile iron sample.From the sample,the hardness test and composition of element is checked to determine the effect and mechanical properties of different thickness of thin wall ductile iron.